Performance measurement for brain-computer or brain-machine interfaces: a tutorial - Thompson, David E.; Quitadamo, Lucia R.; Mainardi, Luca; Laghari, Khalil ur Rehman; Gao, Shangkai; Kindermans, Pieter-Jan; Simeral, John D.; Fazel-Rezai, Reza; Matteucci, Matteo; Falk, Tiago H.; Bianchi, Luigi; Chestek, Cynthia A.; et al. (My University, 2014)
Objective. Brain–computer interfaces (BCIs) have the potential to be valuable clinical tools. However, the varied nature of BCIs, combined with the large number of laboratories participating in BCI research, makes uniform performance reporting difficult. To address this situation, we present a tutorial on performance measurement in BCI research. Approach. A workshop on this topic was held at the 2013 International BCI Meeting at Asilomar Conference Center in Pacific Grove, California. This paper contains the consensus opinion of the workshop members, refined through discussion in the following months and the input of authors who were unable to attend the workshop. Main results. Checklists for methods reporting were developed for both discrete and continuous BCIs. Relevant metrics are reviewed for different types of BCI research, with notes on their use to encourage uniform application between laboratories. Significance. Graduate students and other researchers new to BCI research may find this tutorial a helpful introduction to performance measurement in the field.
Keywords: Brain–computer interfaces; Performance measurement; 2013 International BCI Meeting